Análisis del control interno para la optimización de los recursos en la comercialización de la merma de banano en las haciendas mariazita y konita de la compañía bananera las mercedes S.A. del cantón Valencia, año 2010 - Bazán Roca, Diana Ivonne (2012)
This research was conducted in the Banana Company SA The Mercedes which has five estates in the canton Valencia, which was considered the Maríazita research, Km 21 via La Maná inning Zapote. Inward and Km 16 Km 21 Konita the Zapote road La Maná 11 Km The planned objectives are a) Analyze the internal control for optimization of resources in the marketing of the decline (rejection) of banana farms and Konita Maríazita Banana Company SA Las Mercedes, b) conduct an assessment of the current status of management and marketing of the decline (rejection) of bananas in the Banana Company The Mercedes SA, c) Investigate the marketing system of reduced (rejection) of bananas in the Banana Company SA The Mercedes d) Establish policies to control the marketing of shrinkage (rejection) of bananas in the Banana Company The Mercedes SA, to develop these objectives it was necessary to apply the exchange bibliographic allowed to develop the theoretical framework, support the issue and the problem research. As data collection techniques was used qualitative and quantitative research through direct observation and interview, to meet the criteria of the Manager, Winemaker and Paymaster, the population was three people is directly related to the marketing of the decline in banana . For the development of the framework was considered secondary sources by relying on books, theses and internet among others, so that they contextualize and substantiate the independent and dependent variables under study, for it is considered the most important concepts and definitions of Internal Control , the same is connected with the object of investigation.